2010
DOI: 10.1017/s0007485310000167
|View full text |Cite
|
Sign up to set email alerts
|

Cross-amplified microsatellites in the European cherry fly,Rhagoletis cerasi: medium polymorphic–highly informative markers

Abstract: The European cherry fruit fly, Rhagoletis cerasi (Diptera: Tephritidae), is a major pest of cherries in Europe and parts of Asia. Despite its big economic significance, there is a lack of studies on the genetic structure of its natural populations. Knowledge about an insect pest on molecular, genetic and population levels facilitates the development of environmentally friendly control methods. In this study, we present the development of 13 microsatellite markers for R. cerasi, through cross-species amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…To separate environmental from genetic factors contributing to the potential variation in diapause intensity among the three populations, their genetic structure should be considered. Using microsatellite markers, it has recently been revealed that the two Greek populations used in our study form one cluster with moderate levels of gene flow, whereas the German population is quite different from the previous cluster (Augustinos et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…To separate environmental from genetic factors contributing to the potential variation in diapause intensity among the three populations, their genetic structure should be considered. Using microsatellite markers, it has recently been revealed that the two Greek populations used in our study form one cluster with moderate levels of gene flow, whereas the German population is quite different from the previous cluster (Augustinos et al ., , ).…”
Section: Methodsmentioning
confidence: 99%
“…Microsatellites are a class of highly polymorphic molecular markers widely distributed in the genome of eukaryotes that can be useful to clarify such patterns of gene flow and to identify the spatial locations of genetic discontinuities (population boundaries) in studies of species complexes (Chambers and MacAvoy 2000, Barbará et al 2007, Aketarawong et al 2014). Within the Tephritidae, microsatellites have been successfully developed and applied for several Bactrocera species (Shearman et al 2006; Aketarawong et al 2006, 2007, Augustinos et al, 2008, Virgilio et al 2010; Drew et al 2011), for Rhagoletis cerasi L. (Augustinos et al 2011), for a few Ceratitis species (Bonizzoni et al 2001, 2004, Meixner et al 2002, Baliraine et al 2003, 2004, Silva et al 2003, Delatte et al 2013, Virgilio et al 2013), for Anastrepha suspensa (Loew) (Fritz and Schable 2004, Boykin et al 2010), and for Anastrepha obliqua (Macquart) (Islam et al 2011). Microsatellites have only recently been isolated in Anastrepha fraterculus (Lanzavecchia et al 2014) and have proven useful for the analysis of population dynamics and differentiation across the distribution range of this polymorphic species.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using microsatellites have been mainly focused on their use as polymorphic markers in population genetics, genetic diversity, or kinship contexts (reviewed in Schlötterer and Pemberton 1998;Goldstein and Schlötterer 1999). This is particularly true in insects, where reports based on SSR molecular variation are abundant (Insuan et al 2007;Agustinos et al 2011;Blondin et al 2013;Manrique-Poyato et al 2013). In recent years, microsatellite genomic analysis has been powered by the development of high throughput next generation sequencing (NGS) technologies, based on massive sequencing approaches which enable a rapid, low-cost, and low time-consuming way to characterize microsatellites (Malausa et al 2011;Iquebal et al 2013).…”
Section: Introductionmentioning
confidence: 99%